Individual, Community, and Social Network Influences on Beliefs Concerning the Acceptability of Intimate Partner Violence in Rural Senegal - Sandberg, John F. (Journal of interpersonal violence, 2021)
Intimate partner violence (IPV) is a pressing international public health and human rights concern. Recent scholarship concerning causes of IPV has focused on the potentially critical influence of social learning and influence in interpersonal interaction through social norms. Using sociocentric network data from all individuals aged 16 years and above in a rural Senegalese village surveyed as part of the Niakhar Social Networks and Health Project (n = 1,274), we estimate a series of nested linear probability models to test the association between characteristics of respondents’ social networks and residential compounds (including educational attainment, health ideation, socioeconomic status, and religion) and whether respondents are classified as finding IPV acceptable, controlling for individual characteristics. We also test for direct social learning effects, estimating the association between IPV acceptability among network members and co-residents and respondents’ own, net of these factors. We find individual, social network, and residential compound factors are all associated with IPV acceptability. On the individual level, these include gender, traditional health ideation, and household agricultural investment. Residential compound-level associations are largely explained in the presence of the individual and network characteristics, except for that concerning educational attainment. We find that network alters’ IPV acceptability is strongly positively associated with respondents’ own, net of individual and compound-level characteristics. A 10% point higher probability of IPV acceptability in respondents’ networks is estimated to be associated with a 4.5% point higher likelihood of respondents being classified as finding IPV acceptable. This research provides compelling evidence that social interaction through networks exerts an important, potentially normative, influence on whether individuals in this population perceive IPV as acceptable or not. It also suggests that interventions targeting individuals most likely to perceive IPV as acceptable may have a multiplier effect, influencing the normative context of others they interact with through their social networks.